2023
DOI: 10.3389/fneur.2023.1240150
|View full text |Cite
|
Sign up to set email alerts
|

Application of intraoperative ultrasound in the resection of high-grade gliomas

RenJie Wei,
Hao Chen,
YuXiang Cai
et al.

Abstract: The incidence of gliomas is approximately 3–5/100,000, with high-grade gliomas accounting for approximately 30–40% of these tumors. Surgery is a confirmed positive factor in prolonging the survival of these patients, and a larger resection range means a longer survival time. Therefore, surgery for high-grade glioma patients should aim to maximize the extent of resection while preserving neurological function to achieve a better quality of life. There is consensus regarding the need to lengthen progression-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Various authors have demonstrated in patients with brain tumors an increase in survival time related to the degree of tumor resection [26,27]. Moreover, recent publications have shown that intraoperative ultrasound provides better information about the extent and location of the tumor, facilitating the neurosurgeon's orientation during its excision [28,29]. Intraoperative ultrasound also aims to complement neuronavigation images, whose validity decreases when there is a displacement of brain tissue during tumor resection, a phenomenon known as "brain shift" [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various authors have demonstrated in patients with brain tumors an increase in survival time related to the degree of tumor resection [26,27]. Moreover, recent publications have shown that intraoperative ultrasound provides better information about the extent and location of the tumor, facilitating the neurosurgeon's orientation during its excision [28,29]. Intraoperative ultrasound also aims to complement neuronavigation images, whose validity decreases when there is a displacement of brain tissue during tumor resection, a phenomenon known as "brain shift" [24].…”
Section: Discussionmentioning
confidence: 99%
“…Detecting a possible tumor remnant during surgery can mean significant time and cost savings for the patient, avoiding a possible surgical reintervention [28][29][30][31][32]. Finally, intraoperative ultrasound is a technology that is less costly compared to other studies such as intraoperative MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the rate of complete surgical resection (CSR), numerous advanced therapeutic techniques have been developed, such as multimodal MRI, intraoperative MRI (IoMRI), intraoperative ultrasound, and fluorescence-guided surgery [240][241][242] Despite extensive post-surgical management, the complete eradication of disseminated tumor cells around the tumor cavity remains unachievable under microscopic observation. Intraoperative radiation therapy (IORT) represents a strategic approach involving the application of high-dose radiation directly to the residual tumor bed during surgery.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Local recurrence is a principal factor contributing to the malignant progression of GBM in clinical settings, with the majority of recurrences occurring within a limited margin (2 to 3 cm) surrounding the tumor cavity. To enhance the rate of complete surgical resection (CSR), numerous advanced therapeutic techniques have been developed, such as multimodal MRI, intraoperative MRI (IoMRI), intraoperative ultrasound, and fluorescence-guided surgery [ 240 , 241 , 242 ]…”
Section: Surgical Treatmentmentioning
confidence: 99%